Text and context in the history,literature and religion of Orissa - Malinar, Angelika; Frese, Heiko; Beltz, Johannes (Studies in Orissan society, culture and history, 2004)
Contributed articles on culture of Orissa
Keywords: Odisha (India) -- Civilization; Orissa; Südasien; Aufsatzsammlung; Kontext; Literatur; Religion; Kultur; Odisha